2017
DOI: 10.1016/j.jbiotec.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of a three step mAb chromatography process from batch to continuous: Optimizing productivity to minimize consumable requirements

Abstract: The goal of this study was to adapt a batch mAb purification chromatography platform for continuous operation. The experiments and rationale used to convert from batch to continuous operation are described. Experimental data was used to design chromatography methods for continuous operation that would exceed the threshold for critical quality attributes and minimize the consumables required as compared to batch mode of operation. Four unit operations comprising of Protein A capture, viral inactivation, flow-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…These savings come entirely from the consumables category, which includes Protein A sorbent and prepacked columns, as well as buffer preparation and storage bags. The Cadence BioSMB system allows for significant increases in sorbent productivity and reductions in buffer utilization over single column chromatography . This translates to reduced Protein A volume and buffer storage requirements over the batch processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These savings come entirely from the consumables category, which includes Protein A sorbent and prepacked columns, as well as buffer preparation and storage bags. The Cadence BioSMB system allows for significant increases in sorbent productivity and reductions in buffer utilization over single column chromatography . This translates to reduced Protein A volume and buffer storage requirements over the batch processes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to enabling continuous operation, the Cadence Acoustic Separator allows for a significant reduction in clarification depth filtration area. The Cadence BioSMB is a form of multi‐column chromatography system that enables continuous operation and reduced sorbent volume via secondary loading columns and parallel column regeneration . The Cadence BioSMB model utilized the same experimental breakthrough data as the batch bind and elute models, but loading was assumed to be 80% of the volume required to reach 10% breakthrough, corresponding to approximately 1% breakthrough.…”
Section: Methodsmentioning
confidence: 99%
“…Several purification steps have been developed or modified for continuous operation. The most pragmatic and simplest approach is to break down a unit operation into small sub‐processes and perform them in a cyclic or periodic manner (Gjoka, Gantier, & Schofield, 2017; Godawat et al, 2012; Jungbauer, 2013; PALL, 2018; Warikoo et al, 2012). However, with such an approach a discontinuous or discrete outflow is obtained, which renders process integration cumbersome or even impossible without numerous surge tanks.…”
Section: Introductionmentioning
confidence: 99%
“…With the need to balance, the cost of raw materials against production costs, organizational design (shift management) and commercial demand, biomanufacturing facilities have come under pressure to improve the efficiency of their downstream manufacturing process. For this purpose, integrated continuous downstream processing is considered as a potential solution to reduce operational costs, increase efficiency and flexibility, streamline processes, reduce footprint, and improve product consistency and quality (Bisschops & Brower, ; Gjoka, Gantier, & Schofield, ; Hernandez, ; Jacquemart et al, ; Warikoo et al, ).…”
Section: Downstream Platform Processmentioning
confidence: 99%
“…In another study, an integrated downstream bioprocess delivering purified mAb product was demonstrated using a 25 L fed‐batch bioreactor (Gjoka et al, ). An eight‐column ProA (5‐cm bed height) process at a linear flow velocity of 360 cm/hr was used to capture the mAbs.…”
Section: Continuous Downstream Processingmentioning
confidence: 99%